Java, Facts and Fancies - Wit, Augusta de, 1864-1939 (Salt Lake City, UT : Project Gutenberg, 2013)
"Java, Facts and Fancies" by Augusta de Wit is a descriptive travelogue written in the early 20th century. The book vividly captures the author's experiences and observations during her time in Java, highlighting the natural beauty, culture, and daily life of the area. With 160 illustrations accompanying the text, it promises an immersive journey through the landscapes and society of Java. At the start of the narrative, the author reflects on her initial misconceptions about Java, viewing it as a fantastical land filled with dreams and fancies. She describes her arrival during the rainy season, where the scene is painted with soft hues and delicate natural elements, contrasting sharply with the more tumultuous realities of the environment. The opening portion depicts her first impressions of Batavia, showcasing the unique blend of local customs, tropical settings, and the numerous native boats that populate the waters, creating an enchanting yet complex portrait of life in this vibrant region. (This is an automatically generated summary.)
Release date is 2013-09-07
E-text prepared by Walt Farrell, Marc-André Seekamp, David Garcia, Marilynda Fraser-Cunliffe, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Java (Indonesia) -- Description and travel; Java (Indonesia) -- Social life and customs